2009
DOI: 10.1007/s12088-009-0016-y
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of phosphate solubilizing bacteria in rhizosphere of chickpea, mustard and wheat grown in different regions of Haryana

Abstract: The native population of phosphate solubilizing bacteria (PSB) was studied in the rhizosphere of chickpea, mustard and wheat grown in different regions of Haryana. A total of 193 PSB were isolated from 245 rhizospheric samples collected from south-west and north-east zones. The PSB count showed large variations (3-67 × 10 5 cfu/g) and biodiversity within the crop and place of sampling. Using biochemical analysis, the isolates were tentatively identifi ed as belonging to four genera, Pseudomonas, Aeromonas, Kle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 12 publications
5
28
1
2
Order By: Relevance
“…Also, similar results have been reported in Kenyan soils with a number between 0.38 and 9.1 × 10 5 CFU g −1 of soil [19] and in Chinese soils from 6 to 22 × 10 5 CFU g −1 of soil [46]. However, other studies have reported higher values than ours, such as soils under crop-pasture rotations in a no-tillage regime in Uruguay with 0.65-62 × 10 5 CFU g −1 soil [20] and 3-67 × 10 5 CFU g −1 soil in the rhizosphere of chickpea, mustard, and wheat grown in different regions of Haryana in India [47]. On the contrary, very low numbers have been reported in northern Spain with an abundance of PSB lower than 10 2 CFU g −1 soil [48], in Argentina between 0.03 and 0.08 × 10 5 CFU g −1 of soil [21], and in northern Karnataka in India from 0.01 to 0.18 × 10 5 CFU g −1 of soil [49].…”
Section: Discussioncontrasting
confidence: 73%
“…Also, similar results have been reported in Kenyan soils with a number between 0.38 and 9.1 × 10 5 CFU g −1 of soil [19] and in Chinese soils from 6 to 22 × 10 5 CFU g −1 of soil [46]. However, other studies have reported higher values than ours, such as soils under crop-pasture rotations in a no-tillage regime in Uruguay with 0.65-62 × 10 5 CFU g −1 soil [20] and 3-67 × 10 5 CFU g −1 soil in the rhizosphere of chickpea, mustard, and wheat grown in different regions of Haryana in India [47]. On the contrary, very low numbers have been reported in northern Spain with an abundance of PSB lower than 10 2 CFU g −1 soil [48], in Argentina between 0.03 and 0.08 × 10 5 CFU g −1 of soil [21], and in northern Karnataka in India from 0.01 to 0.18 × 10 5 CFU g −1 of soil [49].…”
Section: Discussioncontrasting
confidence: 73%
“…Phosphorus can be found in nature as organic and mineral forms (Kundu et al 2009). The concentration of soluble P in soil is very low, varying from 0.001 mg L -1 in very poor soils to 1 mg L -1 in heavily fertilized soils.…”
Section: Screening Cabbage Rhizosphere As a Habitat For Isolation Of mentioning
confidence: 99%
“…Many microorganisms in the soil are able to solubilize insoluble forms of Ca-bound P by excreting organic acids that either dissolve RP directly or chelate Ca 2+ ions to bring the P i into solution (Katznelson and Bose 1959), or by producing various siderophores, mineral acids, protons, humic substances, CO 2 and H 2 S. This phenomenon of solubilizing insoluble inorganic phosphates by microorganisms is known as 'mineral phosphate solubilization' (Goldstein 1986). The important genera of phosphate-solubilizing bacteria (PSB) include Achromobacter, Aerobacter, Alkaligenes, Bacillus, Pseudomonas, Serratia and Xanthomonas, Aeromonas, Klebsiella, Enterobacter (Chen et al 2006;Kundu et al 2009). In addition, certain fungi known as phosphate solubilizing fungi (PSF) have also been shown to solubilize insoluble phosphate (Rajankar et al 2007).…”
Section: Introductionmentioning
confidence: 99%